Pengaruh Faktor Predisposisi, Pemungkin dan Kebutuhan Terhadap Pemanfaatan Pelayanan Jaminan Persalinan di Wilayah Kerja Puskesmas Parongil Kabupaten Dairi - Sirait, Betty; Juanita, Juanita; BZ, Heldy; Triana, Neni (JURNAL KESEHATAN TERAPAN, 2024)
World health problems that cannot be resolved include maternal mortality, maternity and infant mortality. How to reduce the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) with MDG's. National MMR (2017) is 228/100,000 KH and IMR is 34/1,000 KH. Dairi Regency MMR (2020) is 209/100,000 KH and IMR 14/1,000 KH. The aim of the research is to analyze the influence of predisposing, enabling and need factors on the utilization of Maternity Insurance services in the Working Area of ​​the Parongil Health Center, Dairi Regency. This type of research is explanatory research. The total sample was 95 mothers giving birth. Data analysis includes univariate, bivariate analysis with chi square, Fisher and multivariate tests with multiple logistic regression. The results of the research were that 30.53% of respondents utilized Maternity Guarantee services and 69.47% of respondents did not utilize Maternity Guarantee services. The results of the chi-square and Fisher tests show that there are 3 variables that are significantly related to the utilization of Maternity Insurance services where the p value is <0.005, namely knowledge (p<0.001), facilities (p<0.001) and needs (p<0.001). From the results of the multivariable multiple logistic regression, the most influential influence on the utilization of Maternity Insurance services is the facilities.